Exploring the effects of Lisdexamfetamine (Venvanse) on students: Perspectives on Attention Deficit Hyperactivity Disorder (ADHD), Binge Eating Disorder (BED), and associated complications (Research, Society and Development, 2025)
Lisdexamfetamine dimesylate (LDX) is a prodrug widely used in the treatment of attention deficit hyperactivity disorder (ADHD) and binge eating disorder (BED). Despite its therapeutic efficacy, concerns regarding misuse, adverse effects, and interactions with other psychiatric conditions have been increasing, especially among students. To conduct a systematic review on the benefits, mechanisms of action, complications, and patterns of non-medical use of LDX, focusing on student populations, aiming to guide safer prescribing practices. Following PRISMA guidelines, databases such as PubMed, SciELO, and Medline were consulted using search strategies with Boolean operators and keywords related to LDX, ADHD, BED, and misuse. Clinical studies, systematic reviews, and case reports published between 2019 and 2024 were included, while theses and unpublished data were excluded. LDX demonstrated significant efficacy in reducing binge eating episodes (up to 64%) and ADHD symptoms (40% improvement in assessment scales). However, a high risk of non-medical use was identified among students (7.8% in North American universities), associated with cardiovascular complications, overdose, and dangerous interactions with antidepressants. Its mechanism of action involves dopaminergic and noradrenergic modulation, with a superior safety profile compared to traditional amphetamines, though still subject to adverse effects such as hypertension, tachycardia, and insomnia. Lisdexamfetamine is an effective therapeutic option for ADHD and BED; however, its use requires rigorous monitoring, patient education, and more effective regulation to mitigate risks of misuse and complications, especially in academic settings.